Primary School Teachers' Personal and Professional Beliefs on Diversity - Željka Knežević (Center for Educational Policy Studies Journal)
The paper presents research conducted among Croatian primary school classroom teachers and subject teachers regarding their personal and professional beliefs about diversity. The notion of diversity in the context of education was presented as individual differences between students based on race, ethnicity, religious beliefs, gender, abilities, sexual orientation and social class. The results indicate that teachers show different levels of openness towards certain aspects of diversity in the domains of both personal and professional beliefs, but that their personal beliefs are statistically more positive than their professional beliefs. Differences in teachers' beliefs with respect to years of work experience, previous education and professional position were also examined. Statistically significant differences were established only regarding professional position and only in the segment of professional beliefs. The results indicate that there is a need for further research in this area, that is, research that primarily investigates the factors that influence teachers' professional beliefs.